THE EFFECT OF SIDERATE CROPS AND MINERAL FERTILIZERS RATE ON SOIL WATER PERMEABILITY - Khalikov Bakhodir Meylikovich; Ganiev Sanjar Ernazarovich (Journals Park Publishing, 2023)
In the experiment, the water-physical properties of the soil were improved due to the use of manure and mineral fertilizers on the background of siderate crops and the application of manure and mineral fertilizers in the conditions of moderately saline sierozem soils of the Jizzakh region N-160, P2O5-112, K2O-80 kg/ha and in addition 20 t/ha of manure under the plow, the best result was obtained in option 7. At the end of the application period, the water permeability of the soil is 6 hours, it was 887 m3 /ha.. This is more than 108 m3 /ha compared to the control. Therefore, in the conditions of medium salinity soils, water passage in this norm improves the salt balance and creates favorable conditions for plant growth and development.
Keywords: average salinity, being meadow sierozem soils, water permeability, siderate crops, manure, mineral fertilizers, rate, ratio.